حق الزوج في التعويض عن فك الرابطة الزوجية بالخلع - بشير, راضية; لنكار, محمود (جامعة الوادي University of Eloued, 2019)
لما صارت الزوجة صاحبة حق خالص وأصيل فيما تعلق بالخلع، يقابل حق الزوج في الطلاق بإرادته المنفردة؛ فإن احتمال تعسفها فيه وخروجها عن سلوك الزوجة السوية وارد، واحتمال تضرر زوجها منه أيضا وارد وبشدة. لكن ورغم ذلك، فالمشرع الجزائري لم يفرض عليها أي تعويض، بل بالعكس من ذلك، فقد أعفاها من تسبيب طلبها له، فيكفي أن تؤسسه على كونها لا تطيق زوجها فحسب -سواء كان ذلك صحيحا أم لا- وبالتالي إقصاء عبارة التعسف من دائرتها مطلقا، مما ينجر عنه حرمان الزوج من إمكانية مطالبته بالتعويض عن الضرر الذي قد يلحقه. وكل ما ألقاه المشرع على كاهلها، هو مجرد بدل الخلع -المقنن مسبقا عند عدم الاتفاق حوله- والذي لا يرقى إلى مصاف التعويض بمعنى الكلمة. The wife by becoming a holder of a pure and original right relative to the divorce in front of the right of the husband in the divorce by his unilateral will probably lead the wife to abuse and deviate from the conduct of the normal wife and could affect seriously the husband. However the Algerian legislator did not impose her any compensation for the harm suffered, he rather exempted her from giving the reasons of her claim where she has only to base it on the fact that she does not bear her husband, which can be true or false. Consequently, this excludes totally the term “abuse” towards her and entails the deprivation of the husband of the possibility to claim damages for the harm suffered. In fact, the legislator demanded only a payment for the khula’ -that is previously codified for the case of disagreement upon its amount- and which does not reach the level of compensation in the true sense of the term.
the Right Of The Husband To Damages Due To Divorce By Khula
Keywords: الخلع ; بدل الخلع ; التعويض; التعسف ; الضرر; khula ; 'payment for khula ; damges ; abse ; harm